The Relationship between Chronic Diseases and Cognitive Function in Patient with Chronic Diseases: An Analysis Based on the 2014 Indonesian Family Life Survey Data - Fira Awanis Hazrina; Rohman Azzam; Yani Sofiani; Yuni Shahroh; Bayu Satria Wiratama; Ninik Yunitri (GLOBAL HEALTH SCIENCE GROUP, 2026)
Cognitive decline known as one of long-term effect of chronic disease. Individuals with cognitive dysfunction tend to show low quality of life. Yet limited studies has been conducted to determine the prevalence of this issue among people with chronic disease in Indonesia. Therefore, this study was aimed to identify the prevalence and relationship between chronic disease and cognitive function. This study also evaluated the factors influencing this relationship. This research was a cross-sectional analysis that utilized data from 2,396 participants with chronic conditions, drawn from the 2014 Indonesian Family Life Survey (IFLS) through purposive sampling. This study focus on people with hipertention, stroke, and diabetes mellitus. Cognitive impairment was measured using Telephone Interview for Cognitive Status (TICS). The data was analysed using analysed using bivariate logistic regression and multivariate Hierarchical Logistic Regression. The relationship between variables indicated based on Odds Ratio (OR), exponential value values ꞵ (eꞵ), and significancy level 5%. The overall prevalence of impaired cognitive function was 2171(61.7%) with the highest frequency found in people with diabetes mellitus (64.5%). Logistic regression test found a significant relationship between chronic disease and impaired function (p<0.001). Hierarchical Logistic Regression test on all models found-that age, gender, disease duration, and education had a greater influence, with R2 0.467 (46.7%). This study showed people with chronic diseases with older age, female, low education, longer disease duration, smoker, and obese have higher risk of developing impaired cognitive function.